One Stage Reconstruction and Refinements for Frontonasal Encephalocele (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: The successful correction of frontonasal encephaloceles was shown to depend on a detailed understanding of the pathological anatomy, careful planning of the bone movements to correct these deformities, and attention to detail regarding the placement of scars, positioning of the medial canthi and the nasal reconstruction.Objective: We reviewed our experience at the paediatric neurosurgery department of national institute of neurosciences, Dhaka, Bangladesh and discussed our evolution toward a definitive, single-stage correction, including refinements.Methodology: This was a clinical trial which was conducted in the Department of Paediatric neurosurgery at National institute of Neurosciences & Hospital, Dhaka, Bangladesh fromMay 2014 to April 2019 for a period of five (05) years. Paediatric patients with frontonasal encephalocele were operated. Post-operative outcomes were observed.Result: A total number of 6 patients were operated. All were under 1 year. 3 were male and 3 were female. We operated 6 cases of successful one stage operation for frontonasal encephalocele in very young children. A good cosmetic result had been achieved after operation.Conclusion: In conclusion, a one-stage repair with both a transcranial and external approach is effective surgical management for the frontonasal encephalocele paediatric patients.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 111-117